2020
DOI: 10.1080/21623945.2020.1834230
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated gene knockout in human adipose stem/progenitor cells

Abstract: The CRISPR/Cas9 system is a powerful tool to generate a specific loss-of-function phenotype by gene knockout (KO). However, this approach is challenging in primary human cells. In this technical report, we present a reliable protocol to achieve a functional KO in the genome of human adipose stem/progenitor cells (ASCs). Using Sprouty1 (SPRY1) as a model target gene for a CRISPR/Cas9 mediated KO, we particularize the procedure including the selection of the CRISPR/ Cas9 target sequences and the employment of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…These findings were similar to previous study that found a decrease in the expression of AhR and its downstream genes in KO cells utilizing CRISPR/Cas9 technology (Zgarbová & Vrzal, 2022). Disrupting specific genes in stem cells through knockout techniques is a highly effective method for investigating their roles in differentiation, proliferation, and other essential cellular functions (Mandl et al, 2020). Several genome editing methods have been developed to generate KO stem cells, with CRISPR/Cas9 is one of the most powerful systems (Kim et al, 2020;Lee et al, 2022).…”
Section: Expression Levels Of Genes In Ahr-ko Cell Clonessupporting
confidence: 89%
“…These findings were similar to previous study that found a decrease in the expression of AhR and its downstream genes in KO cells utilizing CRISPR/Cas9 technology (Zgarbová & Vrzal, 2022). Disrupting specific genes in stem cells through knockout techniques is a highly effective method for investigating their roles in differentiation, proliferation, and other essential cellular functions (Mandl et al, 2020). Several genome editing methods have been developed to generate KO stem cells, with CRISPR/Cas9 is one of the most powerful systems (Kim et al, 2020;Lee et al, 2022).…”
Section: Expression Levels Of Genes In Ahr-ko Cell Clonessupporting
confidence: 89%
“…Employment of specific shRNAs abolished ARNTL2 mRNA expression but failed to significantly reduce the corresponding protein level (data not shown). A CRISPR/Cas9-mediated gene knockout approach, as recently described by us [58], was ineffective despite the use of several target sequences (data not shown). The failure of both techniques to profoundly reduce the ARNTL2 protein level in ASCs is most likely due to the very high stability of this transcription factor (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Identification of surrogate markers relevant to functionality would therefore go a long way towards developing more effective therapeutic regimes. Efforts have been made to associate RNA or protein signatures with clinically relevant properties [ 20 , 21 , 22 , 23 ], but surface markers provide advantages that defined subpopulations may be purified and investigated [ 12 ]. Some surface markers, mostly CDs studies as a single epitope or in a limited co-expression pattern, have been previously proposed to support certain biological functions early after isolation [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%